Acoustofluidic trapping device for high-NA multi-angle imaging - Løvmo, Mia Kvåle; Moser, Simon; Thalhammer-Thurner, Gregor; Ritsch-Marte, Monika (Frontiers in Physics, 2022)
In the life sciences, there has been growing awareness that the traditional 2D cell culture model has its limitations in advancing our understanding of the mechanisms that underlie cell behavior, as the behavior and response of cells depend on the 3D microenvironment. Studying models such as suspended cell clusters and organoids is a step toward closing the gap between in vitro and in vivo studies. The fact that sample confinement and contact with surfaces have an impact on cells creates a need for contact-less tools for the inspection of live biological samples. Recently, we developed an acoustofluidic chip to trap and manipulate sub-millimeter-sized biological samples, and here, we demonstrate that this device can be adapted to support high-resolution imaging and illumination scanning for multi-view image acquisition. After coupling acoustic bulk waves into a microfluidic chip, the sample is levitated by an optically transparent transducer in the vertical direction. Two orthogonal side-transducers give additional control over the sample. By tuning the relative strengths of the three transducers and thus inducing an acoustic torque, we can transiently rotate the sample into various orientations for image acquisition. Under different operating conditions, exciting other modes, we can also induce sustained rotation of samples by means of other torque contributions and around axes perpendicular to the imaging axis, which is important to avoid “missing cone” artifacts in the tomographic reconstruction of the sample. We will discuss the modifications to our previously established device that were necessary to comply with the requirements for high-NA imaging and high-NA illumination. We provide a characterization of the performance and show examples of rotation and reorientation of biological samples, such as large pollen grains and cancer spheroids.